BIOGRAFI K.H. DJAMALUDDIN AMIN DAN PEMIKIRANNYA - Mujizatullah Mujizatullah (EDUCANDUM, 2018)
The study aims to reveal how the biography of KH Djamaluddin Amien'scharacter tells about his life. Biography can be seen that he does not want to becultivated as a kyai and generator of educational social movements, includingthrough schools built from TK / TPQ Raudhatul Athfal, Elementary Schools,Madrasah Tsanawiyah and Madrasah Aliyah, and the mosque in the land ofKaraeng Bissoloro, Gowa Regency. His biography can also be seen from histhoughts and works in the world of education, activities as the leader of theMuhammadiyah of South Sulawesi Region, as Chancellor of the MuhammadiyahUniversity of Makassar, and as Chair of the National Mandate Party eventhough he does not want to be a member of the DPR. The mandate is held at thesame time. This study uses a qualitative research approach, supplemented byliterature studies and interviews. The results showed that the personality of KHDjamaluddin Amien as a cleric and Muhammadiyah figure in South Sulawesihad its own characteristics. The thought in the field of religious education is therenewal of the curriculum and teaching methods by combining the teachingmodel of K.H. Ahmad Dahlan with K.H.Hasyim Asy'ari, and charactereducation models through religious extracurricular activities that combineelements of religious science and general sciences with classical systems. Theconcept of multicultural education that was built by him was open to change,prioritizing discussion and dialogue. In Religious Education, he taught the kitabkuning which was held every night Wednesday and Friday. The method appliedis the Sorogan and Bandongan methods